Brief Lifestyle of Malay Adolesecents - Dahar, Zainurin bin; Salleh, Zurilawati binti (International Journal of Engineering and Technology, 2018)
The research is to explore briefly the lifestyle of Malay adolescent in terms of buying habits, fashion preference, interest, activities, time management and self-perception. The previous literatures have found that adolescents’ population have been increasing substantially. Their influenced over shaping the business focus and environment is getting stronger as their consumption in term of dollar is getting more significant. The knowledge of their lifestyle and behavior is vital for marketers as they have becoming the future potential and lucrative target market. We have conducted self-administered survey for data collection. Approximately ninety respondents have completed the self-administered questionnaires. The finding of this study has shown that fashion and self-perception have significant relationship with Malay adolescents lifestyle.